Study of role of oral probiotics in patients on ventilator in paediatric Intensive Care Unit at tertiary care center - Chawan, Prashant; Rajan, Aswathy (International Journal of Contemporary Pediatrics, 2020)
Background: The normal intestinal microbiota of critically ill patients is altered and replaced by pathogens. Any significant insult to the gut or alteration to its microbiota plays a role in promoting systemic inflammation and infection in the critically ill population. Probiotics may affect other body sites in addition to the GI tract , and they can have applications in a variety of populations, including healthy individuals, children, elderly, immunocompromised and genetically predisposed individuals. These studies the effect of probiotics in pediatric population on mechanical ventilation in a tertiary care hospital. Methods: Present study was conducted in a PICU of a tertiary care teaching hospital in children aged 12 years or less admitted to PICU and who were likely to need mechanical ventilation for more than 48 h were recruited. Results: In present study 25 patients were recruited in each group i.e. case (probiotics) group and control group. Most common age group among case group was 6-8 years (44 %), while 9-12 years (36 %) was most common age group in control group. Mean age was comparable in both groups (7.6±3.5 years in case group and 7.9±4.1 years in control group). In both groups septic shock and pneumonia were most common diagnosis followed by admission due to miscellaneous cause. In both groups mechanical ventilation was used due to respiratory failure and shock. Outcome was compared in both groups. Authors noted a statistically significant difference in duration of ICU stay, duration of hospital stay and duration of mechanical ventilation, between case 7 control group (p<0.05). In terms of overall mortality, authors did not noted any significant difference among groups. Conclusions: Authors noted a statistically significant difference in duration of ICU stay, duration of hospital stay and duration of mechanical ventilation, between case and control group (p<0.05).